Beckman Introduces New Dissolved Oxygen Monitors - Schwanbeck, Mark (1976)
The press release describes the features of two new models: the 7001, intended for use in applications such as desalination, and the 7002, designed for continuous monitoring of streams, rivers, and industrial effluents. Developed from a Linus Pauling design during WWII, the technology behind Beckman Instruments’ oxygen analyzers ended up doing such diverse jobs as monitoring astronauts’ respiration, maintaining packaged food safety, and preventing blindness in newborn babies.
Keywords: Water--Dissolved oxygen--Measurement; Scientific apparatus and instruments; Oxygen--Measurement; Oxygen--Analysis; Beckman Instruments, Inc.